ANALISIS TENTANG MANFAAT KEIKUTSERTAAN MAHASISWA FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN DALAM ORGANISASI KEMAHASISWAAN SE-LINGKUNGAN FKIP UNIVERSITAS RIAU - Wahyu, M. Hasyir; Erlinda, Sri; Haryono, Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research is motivated by the influence of student organizations in shaping the character of students as potential carriers of change. So that student organizations are considered as the right place to hone soft skills and hard skills of students in order to prepare supplies for the future. Therefore, the authors take the research title "Analysis of the Benefits of Student Participation in the Faculty of Teacher Training and Education in Student Organizations in the Faculty of Teacher Training and Education, Universitas Riau". The purpose of this study was to determine the benefits of the participation of students from the faculty of teacher training and education in student organizations around the FKIP, Universitas Riau and also to determine the factors that encourage students from the Faculty of Teacher Training and Education to participate in student organizations at FKIP, University Riau. The population of this research is FKIP students who are active in the organization, amounting to 1.427 people and the sample of this research is 160 people. The data collection instrument was a questionnaire consisting of 29 questions and an interview consisting of 29 questions. In analyzing the data, the writer used quantitative descriptive. The results of this study indicate that the management of student organizations throughout the FKIP who benefit from participation in student organizations seen from a percentage of 160 respondents as many as 89.57% answered YES where this range is in the "Helpful" category with a range of 51 - 100%. Thus, it can be concluded that the Benefits of Teaching and Education Faculty Student Participation in Student Organizations in FKIP Universitas Riau is Useful.Key Words: Organizations Benefits, Student Organization